EFFECTS OF ILLUMINANCE LEVELS ON SUBJECTIVE BRIGHTNESS PERCEPTION AND OMFORTABILITY IN CHILDREN: STUDY ON AGE-RELATED DIFFERENCES IN SPECTRAL TRANSMITTANCE OF THE CRYSTALLINE LENS - HIGUCHI, Shigekazu; MOTOMURA, Yuki; SHIN, Nakyeong; NAGATA, Kotaro; ETO, Taisuke; OHASHI, Michihiro (Japanese Journal of Physiological Anthropology, 2021)
Effects of illumination light on impression and visual function are likely to depend on the observer’s age. In this study, we compared subjective evaluations of 10 lx, 100 lx and 1000 lx lighting environments in children, adults and elderly subjects. Our results showed that children evaluated the 10 lx and 100 lx lighting environments as more “bright”, “like”, “comfortable” and “easy to see black” than did the other generations. In addition, there was a significant positive correlation between subjective brightness perception and crystalline lens transmittance, though further study is needed to clarify whether crystalline lens transmittance contributes to subjective brightness perception.